(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Le Sharia court: origini, attività e scopi - 2. Alcuni dati statistici - 3. Un’ulteriore evoluzione: l’Arbitration Act e il Muslim Arbitration Tribunal - 4. Il discorso dell’arcivescovo di Canterbury e reazioni - 5. Il Private Members’ Bill della baronessa Cox - 6. La risposta dell’Islamic Sharia Council - 7. Un dibattito ancora in corso: Friend or Foe? Sharia Courts. History and evolution of Muslim courts in the United Kingdom ABSTRACT: In the last thirty years the United Kingdom has experienced the formation and surge of so-called Sharia courts or councils, unrecognised Muslim tribunals with purpose of settling disputes using Islamic religious law. Their stated objectives include providing advice and assistance in the operation of Muslim family life, establishing a bench of scholars to operate as a council, making decisions on matters of Muslim family law, and promoting an enlightened practice of the Muslim faith by Muslims living in the UK. This paper analyses the origins, evolution and functioning of these councils, with emphasis on the lively public debate initiated in 2008 following the Archbishop of Canterbury’s remarks and followed with the bill proposed by Baroness Cox. An overview of the relations between Sharia councils and the State is presented, while providing insight on future scenarios.